CLASSROOM INTERACTION: AN ANALYSIS OF TEACHER'S LANGUAGE CHOICE OF L1 AND TL IN EFL CLASSROOM - Aprianti, Fitri (2014)
This paper presents the results of an investigation of the teacher's language choice that was performed in English as foreign language classroom in one of junior high school in Majalengka. Specifically, the present study is aimed in exploring the division labor between English as the target language (TL) and Bahasa Indonesia as the learners' and the teacher's native language or L1 and the functions of the teacher's L1 use. The available data which consist of transcription of video recordings of the teachers' language choice which were collected during classroom observations were analyzed by using classroom discourse analysis (CLDA). The findings suggest that there is a distinctive pattern of the teacher's language choice in relation to the distribution of the exchange categories. The result shows the target language dominated all of the simple and complex exchange categories. In contrast, the student's first language mainly occurred in complex exchange categories. It signals that the students' first language commonly occurred whenever problem or trouble happen. Thus, it can be concluded that English has always been a part of the exchange categories. Teacher mainly used the target language as the initiation in every exchange, however whenever trouble occur it was the students first language or that was used, in the other word, the students first language mainly used as the evaluative turn of the exchange itself. The use of L1 in a form of both synoptic and dynamic moves was employed in order to keep the flow of information channel open.